Capital Buffers and Bank Risk: Empirical Study of Adjustment of Pakistani Banks - Noreen, Umara; Alamdar, Fizza; Tariq, Tabassum (International Journal of Economics and Financial Issues, 2016)
Regulatory authorities impose regulations on banks to maintain a threshold of capital to asset ratio above the required minimum level defined by capital adequacy regulation. This research has found important relevancy of bank’s capital buffer and bank risk to the soundness and stability of financial position in banking sector of Pakistan. Present study is gauged to assess the relationship of capital buffer and risk over the business cycle. Panel data of 24 commercial banks has been analyzed over the period of 2007-2012 by applying Generalized Methods of Moments (GMM). The results imply that capital buffers behave pro-cyclically, whereas, bank risk moves counter-cyclically to the economic cycle. The result provides useful insights into effectiveness of regulatory capital minimum and implications of Basel II agreement on the banking industry. This study is valuable for Regulatory authorities in understanding the behavior of banking industry, hence improving the financial health of banking industry and overall economy. Keywords: Basel II, Capital buffers, Bank Risk, Regulation, Panel Data, Generalized Method of Moments (GMM), Pakistan JEL Classifications: G2, G31